(untitled) (Journal of Laboratory Animal Science, 2018)
The purpose of this study was to (a) determine the dosage of cisplatin required to induce intestinal epithelial cell apoptosis, without causing lethality or necrosis and (b) to assess the biochemical changes in intestinal mucosa with different doses of cisplatin administration. A total of 9 WNIN weanling male rats were divided into three groups (n=3). Groups I and II rats were administered low and high doses of cisplatin intraperitoneally (3 and 12 mg/kg body weight) for three weeks, based on computation from human dose while control rats were administered saline intraperitoneally. Morphometric apoptotic counts increased significantly in both villus and crypt regions of the jejunum in animals of group I but not in animals of group II as compared to control. These changes in apoptotic index correlated with enhanced caspase-3 activity and DNA ladder pattern studies. Increased cell death also resulted in loss of functional integrity of the jejunal mucosa and these events were linked to increased oxidative stress and altered antioxidant enzyme activities. A weekly dose of 3 mg cisplatin/kg body weight appeared to induce intestinal epithelial cell apoptosis in WNIN strain, without causing mortality and could be used as a model for determining the therapeutic and cytoprotective potential of novel test candidates.